Mapeamento socioambiental e de sustentabilidade no ambiente escolar - Hennrich Junior, Elio Jacob (2016)
This scientific paper investigated the daily rise of the need to adapt to a routine of several environmental problems caused by the capitalist economic model that puts in check the future of the environment. Considering this problem, we sought to establish new paths for more sustainable communities through environmental education in formal educational environments. The research sought to analyze in two distinct stages the social-environmental school context lived through the Environmental Education logic. The first stage was to analyze the wider school sustainability scenario of municipal schools of Marechal Cândido Rondon through a social-environmental mapping and their related actions to the Environmental Education in the scholar management. Moreover, the second stage of the study was directed to a public school of the city, seeking to understand the social and environmental background thereof, and attempting to work to develop a more complex and holistic building of sustainability in the school environment. The data collection was given through two main tools, the first one conduced was a semi-structured interview with a questionnaire, formulated using open and closed questions that allowed a greater freedom and greater wealth in the research survey research data, allowing a more detailed qualitative and quantitative analysis. Eleven schools In total were investigated, aiming to understand the main characteristics that exists in the school's sustainability levels, such as the level of school sustainability, its vulnerabilities, weaknesses and existing potential in different local realities. In the context that was directed to the particular work with the municipal school, it was sought to carry out actions that would help to establish the culture of school sustainability within the community. As a conclusion a general perspective showed that there is still a large estrangement between the ideal setting for school sustainability and what was found in the formal educational spaces that were analyzed in the research. The paper also showed that implementing a new culture of school sustainability may act directly in the implementation of sustainability concepts throughout the school community